2021
DOI: 10.1192/bjo.2021.1039
|View full text |Cite
|
Sign up to set email alerts
|

Dietary quality and nutrient intake in adults with obsessive–compulsive disorder

Abstract: Background Many mental disorders, including depression, bipolar disorder and schizophrenia, are associated with poor dietary quality and nutrient intake. There is, however, a deficit of research looking at the relationship between obsessive–compulsive disorder (OCD) severity, nutrient intake and dietary quality. Aims This study aims to explore the relationship between OCD severity, nutrient intake and dietary quality. Method A post hoc regression analysis was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
2
3
1
Order By: Relevance
“…This is partly in line with previous research findings showing a significant association between higher obsessive-compulsive symptom severity and lower intake of vegetables and oily fish [ 76 ]. These results contrast with those reported by Nguyen et al [ 24 ], who found no association between OCD severity and dietary quality. Nonetheless, head-to-head comparisons are difficult due to methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is partly in line with previous research findings showing a significant association between higher obsessive-compulsive symptom severity and lower intake of vegetables and oily fish [ 76 ]. These results contrast with those reported by Nguyen et al [ 24 ], who found no association between OCD severity and dietary quality. Nonetheless, head-to-head comparisons are difficult due to methodological differences.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in the United States, almost half of the population (46%) are estimated to have a poor-quality diet [ 68 ]. Nonetheless, most respondents in our survey seemed to have at least relatively healthy dietary habits, in line with the findings by Nguyen et al [ 24 ] on overall dietary quality in OCD, where, in a sample of 85 individuals with OCD, most were considered to meet dietary recommendations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are consistent with the previous literature demonstrating challenges in dietary assessment among individuals with mental illnesses [16,23,47,48]. The high validity of our tailored FFQ addresses the limitations of existing tools and will help advance nutrition research in this population [23].…”
Section: Discussionsupporting
confidence: 89%
“…Elevated triglycerides were found in 25% of patients, which is significantly higher than in the general population (around 10%) [52]. In the literature to date, there are no known links between OCD severity and diet quality or nutrient intake [53].…”
Section: Probable and Possible Organic Ocd Casesmentioning
confidence: 87%